Toxigenicity and phylogeny of Aspergillus section Flavi in poultry feed in Iran - Seyed Soheil Ghaemmaghami; Nasrin Pashootan; Mehdi Razzaghi-Abyaneh (Mazandaran University of Medical Sciences, 2020)
Background and Purpose: This study was conducted to evaluate the presence of aflatoxigenic strains and level of aflatoxin in poultry feed. Aflatoxigenic strains were investigated in corn and soybean meal as the ingredients of poultry feed, as well as in two types of commercial feed, namely pellet and mash. The gene sequencing was performed to identify the species of Aspergillus section Flavi. Materials and Methods: All samples were randomly collected from feed storage silos located in Iran in 2018. The samples were cultured on specialized media for 2 weeks at 28ºC. Identification of Aspergillus section Flavi isolates was based on macro- and microscopic morphological criteria and molecular analysis. The thin-layer chromatography (TLC) was applied to confirm the aflatoxigenic isolates. In addition, the level of aflatoxin B1 (AFB1) produced by these isolates was determined by high-performance liquid chromatography. The strains were subjected to sequence analysis, and Bt2 PCR products were purified by the QIAquick PCR purification kit. At the final stage, the phylogenetic tree was built. Results: Among 54 isolates identified as Aspergillus section Flavi, 20 (37%) isolates were found to produce aflatoxin at a range of 11.28±1.18 to 2239.92±92.26 μg/g fungal dry weight. The aflatoxigenic isolates had the frequencies of 45%, 40%, 10%, and 5% in the corn, pellet, soybean meal, and mash samples, respectively. Furthermore, the mean concentrations of AFB1 were significantly higher in the corn samples (707.04±39.05) than that of other poultry feed samples (P<0.05). A total of 34 (63%) isolates were detected as non-aflatoxigenic on the yeast extract-sucrose broth in TLC analysis. The toxigenic isolates produced the highest (2232.62±55.49) and lowest (11.28±1.18) levels of AFB1 in the corn samples, compared to other feedstuffs. Furthermore, the mean level of AFB1 in mash product was 554.09±10.36 μg/g, compared to a mean level of 229.22±11.09 μg/g in pellets. The isolates were randomly selected, sequenced, and then analyzed. Subsequently, the phylogenetic tree of Aspergillus section Flavi was plotted. Conclusion: The process of converting raw ingredients to compound poultry feed is more hazardous when there is not enough time and temperature provided to eliminate aflatoxigenic isolates. Therefore, Aspergillus section Flavi in poultry feed can pose a threat to the poultry industry and poultry products, thereby affecting the health status of humans. Unprocessed/processed materials, such as corns and pelleted feed, need further monitoring, especially when conditions are not optimal for destroying the fungus.